ANALISIS ABC TERHADAP PERENCANAAN KEBUTUHAN OBAT DI RSUD KOTA YOGYAKARTA TAHUN 2010 - , Heny Puspasari, dr. Sulanto Saleh Danu, SpFK. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background of the Study: Consumption method is one of the standard methods which are used to plan the number of drugs need. This method is providing the good accuracy of the prediction toward the drugs need planning. However, it is not always providing the satisfactory outcome, because this method cannot provide the outlook of the investment value toward each drug. To obtain a plan that suitable to the need and the purpose, so the drug planning can be analyzed by using several methods